Islam Transformatif: Studi Kritik Dan Humanisme (Refleksi Surah Al-Balad) - Muhamad Aroka Fadli (Mufham: Jurnal Ilmu Al-Qur’an dan Tafsir, 2021)
Qur'an was revealed to rescue and liberate humanity from all forms of oppression is a mora, social, cultural, and structural, both in the form of an idea or thought or in the form of praxis. Rescue and Liberation 's history took place in the two pathways, namely the vertical lines and horizontal lines. In the vertical lines, the Qur'an as God's word to the Prophet delivered directly responded to the actual problem that occurs in society at that time. While on Horizontal lines - especially the time of the Prophet and some of Caliph al - Rasyidun Interpretation of the Qur'an through a dialogue with the reality of life in order to give birth to liberation, rescue, and enlightenment for all the problems of social cultural realities that happen. Therefore, the interpretation at first also is transformative - emansifatoris ( frees ) in line with the episteme or guidance and perspective of his day . This paper is about to uncover problems such as the liberation of humanity, the defense of the little people, the tertindas.Pendekatan offered by the mufasirin Contemporary humanity is in resolving problems with the approach of the Social Interpretation.